Lactic acid production by Lactobacillus sp. from biodiesel derived raw glycerol - Prada-Palomo, Yessica; Romero-Vanegas, Marly; Díaz-Ruíz, Pedro; Molina-Velasco, Daniel; Guzmán-Luna, Carolina (CT&F - Ciencia, Tecnología y Futuro, 2012)
Lactic Acid (LA) is a versatile compound with extensive industrial usage. Lactic Acid Bacteria (LAB) are renowned for their capacity to ferment carbohydrates to LA. In the biodiesel industry, bioconversion of residual glycerol to monomers of biopolymers, such as LA, is an alternative for usage of this waste as raw material to produce a high value added biotechnological compound. This research evaluates LA production through fermentation processes using a Lactobacillus sp. native strain and raw glycerol from the biodiesel industry. Native strain was isolated from the processing of dairy, fruit, and vegetable products and through cultures in Man, Rogosa & Sharpe agar (MRS). After an adaptation phase, the fermentative capability of the strain was evaluated through chemical quantification of metabolites using Nuclear Magnetic Resonance (1H-NMR); fermentative potential was compared with a Lactobacillus sp. reference strain (ATCC 7469). The native strain Lactobacillus sp. CYP4 showed a higher bioconversion potential (LA concentration: 39.41 mM, conversion percentage: 39.27%, at 24 h, volumetric productivity: 1.28 g.L-1.h-1, yield: 0.71 g·g-1) from raw glycerol, when compared to the reference strain.